Membangun kepercayaan publik: visualisasi data interaktif capaian kinerja Kantor Regional IX BKN Jayapura - Setiadi, Yusuf; Margono, Hendro; Yuadi, Imam (Jurnal Governansi, 2025)
This research aims to build public trust in the performance of XYZ Regional Office through interactive data visualization using Power BI. Public trust in government agencies is often influenced by transparency and openness in delivering performance information. In this context, interactive and easy-to-understand data visualization is important to improve public understanding of agency performance achievements. The urgency of this research lies in the need for transparency and public accountability, which can encourage active public participation in monitoring and supporting government performance. This research uses a descriptive method with a quantitative approach. The data used is the performance data of XYZ Regional Office, which is then processed and visualized using Power BI. Interactive data visualization is designed to facilitate users in exploring relevant performance information, with a focus on key indicators of agency achievement. By interpreting data findings, this research identifies factors that influence staffing dynamics, such as the total number of civil servants, retirement proposals, and promotion proposals. The implications of the findings are also discussed to provide relevant recommendations for stakeholders related to strategic staffing decision-making. The results showed that the interactive data visualization created was able to increase public understanding and positive perception of the performance of XYZ Regional Office. The novelty of this research lies in the use of Power BI as an interactive visualization tool in the context of government agencies, which has not been widely applied. This research is expected to be a reference for other government agencies to increase public trust through a data-driven approach and performance transparency.